A rare cause of chylous ascites - Chen, Yi-Ting (Clin Kidney J, 2014)
We report a patient with end-stage renal disease status after two renal transplantations. Milky-like ascites was noted since the immunosuppressant agent was switched to sirolimus (1 mg/day). Chylous ascites was diagnosed owing to the triglyceride of dialysate to serum being 15.98:15.99. Series studies were all negative. It is highly suspected that the cause of chylous ascites is sirolimus related because surgically related lymph vessel injury happens most often 6 months after transplantation. Sirolimus-related chylous ascites is a rare cause of chylous ascites but the incidence rate increases after transplantation. Side effects of sirolimus include hyperlipidemia, anemia, thrombocytopenia, hepatotoxicity, delayed wound healing and a high rate of lymphoceles, lymph edema, and pulmonary alveolar proteinosis. Chylous ascitis has improved since the switch from sirolimus to other immunosuppressant agents.